Teori Model Keperawatan Madeleine Leininger - Mursiti Mursiti; Irna Nursanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to explore the application of Madeleine Leininger's transcultural nursing theory in nursing care for patients with diverse cultural backgrounds. The method used is a descriptive case study of a pediatric patient with type 1 diabetes mellitus who refused insulin therapy due to religious and cultural beliefs. The results showed that the application of Leininger's three decision modes—preservation, accommodation, and repatterning—can facilitate negotiations between the patient, family, health care provider, and a third party (a trusted person). The intervention successfully increased the acceptance of wound care according to health standards, although insulin therapy was still refused. In conclusion, Leininger's theory is effective in helping nurses overcome cultural barriers in providing nursing care. The application of this model improves communication, family involvement, and utilization of health facilities, although external support and combination with professional standards are needed for optimal results. Keywords: Cultural Nursing Care, Cultural Values ​​and Norms, Leininger